Among Others : Blackness at MoMA. - English, Darby; Barat, Charlotte; Wilson, Mabel O. (New York : The Museum of Modern Art, 2019)
Adkins, T. ; Akomfrah, J. ; Akunyili Crosby, N. ; Amos, E. ; Anatsui, E ; Andrews, Be. ; Bailey, M. ; Baltrop, A. ; Barrios, A. ; Basquiat, JM ; Bearden, R. ; Beasley, K. ; Lee bendolph, M. ; Bey, D. ; Boghossian, S.; Bourke-White, M. ; Bowling, F. ; Bradford, M. ; Bradley, P. ; Brancusi, C. ; Broodthaers, M. ; Burnett, C. ; Cave, N. ; Chan, P. ; Chase-Riboud, B. ; Clark, E. ; Cole, E. ; Colescott, R. ; Colescott, W. ; Dash, J. ; Decarava, R. ; Delaney, B. ; Dial, T. ; Dimé, M. ; Dine, J. ; Douglas, S. ; Dumas, M. ; Edwards, M. ; Eggleston, W. ; Evans, M. ; Eversley, F. ; Fosso, S. ; Frazier, L. Friedlander, L. ; Gaines, C. ; Gallagher, E. ; Gilliam, S. ; Gober, R. ; Guston, P. ; Hammons, D. ; Harden, M. : Ashton Harris, L. ; Hartt, D. ; Hassinger, M. ; Hayden, P. ; Hendricks, B. ; Hewitt, L. ; Hunt, R. ; Hyppolite, H. ; Jafa, A. ; Julien, I. ; Keïta, S. ; lam, W. ; Lawrence, J. ; Lawson, D. ; Lee, S. ; Levitt, H. ; Lewis, N. ; Lewis, S. ; Ligon, G. ; Linzy, K. ; Lovell, W. ; Loving, A. ; Ray, M. ; Marshall, KJ. ; McMillian,R. ; McQueen,S. ; Mehretu, J. ; Micheaux, O. ; Muholi, Z. ; Muluneh, A. ; Mutu, W. ; Neel, A. ; Nengudi, S. ; Obin, P. ; Ofili, C. ; Oiticica, H. ; Okeke, U. ; Clemente Orozco, J. ; Outterbridge, J. ; Palcy, E. ; Parks, G. ; Patterson, B. ; Peck, R. ; Pendleton, A. ; Perry, S. ; Pindell, H. ; Pippin, H. ; Portinari, C. ; Purifoy, N. ; Puryear, M. ; Riggs, M. ; Ringgold, F. ; Rowland, C. ; Saar,B. ; El-Salahi, I. ; Samba, C. ; Satterwhite, J. ; Saunders, R. ; Segall; L. ; Sembène, O. ; Serra, R. ; Shonibare, Y. ; Sidibé, M. ; Simmons, G. ; Simmons, X. ; Simpson, L. ; Smith, M. ; Syms, M. ; Taylor, H. ; Thomas, A. ; Thompson, B. ; Tuymans, L. ; Valentim, R. ; Van Der Zee, J. ; Walker, K. ; Wall, J. ; Mae Weems, C. ; White, C. ; Whitten, J. ; Williamson, S. ; Wilson, F. ; Yiadom-Boakye, L. ; Yoakum, J.
boek